2007
DOI: 10.1007/s11172-007-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled pseudoliving free-radical polymerization of methyl methacrylate in the presence of butyl-p-benzoquinones

Abstract: Polymerization of methyl methacrylate initiated by dicyclohexyl peroxydicarbonate in the presence of tri n butylboron and butyl p benzoquinone or 2,5 di tert butyl p benzoquinone occurred with no induction period. The yields and molecular masses of the polymers linearly increased with an increase in the conversion degree, which suggests the free radical mechanism of "living" chain polymerization. The poly(methyl methacrylate) macrochains of the prepolymers contained sterically hindered aromatic structures with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The selected p-quinones exhibit different activities in polymerization of vinyl monomers. 50,51,66 With an increase of the inhibition constants of p-quinones their efficiency as agents of controlled polymerization increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected p-quinones exhibit different activities in polymerization of vinyl monomers. 50,51,66 With an increase of the inhibition constants of p-quinones their efficiency as agents of controlled polymerization increases.…”
Section: Resultsmentioning
confidence: 99%
“…14 Besides RAFT agents, a combination of p-quinones with trialkylborane may be used to produce copolymers with desired molecular weight characteristics and microstructures. [49][50][51][52][53] Similar to the systems using atmospheric oxygen, the RDRP mechanism is observed in the presence of p-quinones. However, due to the lack of uncontrolled borane oxidation, a more pronounced control of the polymerization kinetics and molecular weight characteristics of polymers proved to be possible.…”
Section: Introductionmentioning
confidence: 81%
“…The macromolecules that are formed in compliance with Scheme 2, are macroinitiators, they are instrumental in re-initiation of the polymerization according to the reversible inhibition mechanism (Sheme 4) [4,8]:…”
mentioning
confidence: 99%
“…The main advantage of this approach is control of the molecular weight and composition of the forming macromolecules. One of the ways to implement this approach is the use of the tri-n-butylboron-p-quinone catalytic system [3][4][5][6]. The use of this system allows polymerization of some vinyl monomers to be performed in controlled mode (Scheme 1).…”
mentioning
confidence: 99%
“…It has been found that addition of a macroradical to the C=O bond of p-quinone, followed by radical substitution at the boron atom, yields adduct I (macroinitiator), which is capable of reversible homolytic dissociation across the С-О bond [reaction (2)], ensuring the occurrence of the polymerization in the pseudoliving mode [4][5][6][7]. In polymerization of methyl methacrylate (MMA) [3], methyl acrylate, and vinyl acetate in the Scheme 1.…”
mentioning
confidence: 99%